Analisis Strategi Penanganan Pembiayaan Bermasalah Di Baitul Mal Wat Tamwil (BMT) Insani Sadabuan - Putri Maya Sari Harahap; Aswadi Lubis; Hamni Fadlillah Nasution (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
Abstract Non-performing financing can affect BMT Insani Sadabuan's income. From this it requires handling to overcome these problematic financing. The purpose of this research is to find out the strategy for handling problematic financing carried out by Baitul Mal Wat Tamwil (BMT) Insani Sadabuan. This research is a field research with a qualitative approach. The results of the study discuss about financing problems caused by two factors, namely internal factors (originating from BMT Insani Sadabuan) and external factors (originating from members). Handling problematic financing at BMT Insani Sadabuan by contacting members by telephone, direct billing to customer locations, providing Qardul Hasan capital, coaching members, and rescheduling. Keywords: Handling Strategies, Problematic Financing